VIRTUAL SIMULATION AS AN INNOVATIVE METHOD OF FACILITATING VOCATIONAL FOREIGN LANGUAGE ACQUISITION IN HOSPITALITY HIGHER EDUCATION CURRICULUM - E. Perova (Вестник Северо-Кавказского федерального университета)
The article endeavours to research about the implementation of an interactive virtual simulation in vocational foreign language teaching of future specialists in the hospitality industry. In this context, the paper reflects on the theoretical and methodological framework for designing a model of interactive vocational English teaching based on virtual simulation application. By customizing virtual simulations and applying various innovative Internet, computer and mobile technologies, instructors can integrate key didactic principles of the leading methodological systems: behavioral, cognitive, interactive, and communicative ones. As a result, this paper presents a set of core criteria of virtual simulation selection and assessment in vocational foreign language training.